Sensors for Mechatronics - Regtien, P. P. L.; Dertien, Edwin (Elsevier, 2018)
Sensors for Mechatronics, Second Edition, offers an overview of the sensors and sensor systems required and applied in mechatronics. Emphasis lies on the physical background of the operating principles that is illustrated with examples of commercially available sensors and recent developments. Chapters discuss the general aspects of sensors, with a special section on quantities, notations and relations. In addition, the book includes a section devoted to sensor errors and error minimization that apply to most of the sensors discussed. Each subsequent chapter deals with one class of sensors, pursuing a classification according to physical principles rather than measurands. Categories discussed include resistive, capacitive, inductive and magnetic, optical, piezoelectric and acoustic sensors. For each category of sensors, a number of applications is given. Where appropriate, a section is added on the interfacing of the sensor.